2018
DOI: 10.1159/000487560
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-27a Suppresses Detrusor Fibrosis in Streptozotocin-Induced Diabetic Rats by Targeting PRKAA2 Through the TGF-β1/Smad3 Signaling Pathway

Abstract: Background/Aims: We examined the effects of microRNA-27a (miR-27a) on detrusor fibrosis in streptozotocin (STZ)-induced diabetic rats. Methods: Eighty healthy Sprague-Dawley (SD) rats were randomly allocated into control, diabetic, miR-27a mimics, mimics control, miR-27a inhibitors, inhibitors control, siRNA-PRKAA2 (siPRKAA2) and inhibitors + siPRKAA2 groups (the latter 7 groups were established as STZ-induced diabetic rat models and treated in different manners). Detrusor cell apoptosis in bladder tissues was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…In the present study, we found enhanced TGF-β1 facilitated bronchial epithelial cells proliferation in severe asthma. Emerging evidence suggests that miRNAs play a pivotal role in endothelial cells and detrusor fibrosis through the TGF-β1/Smad signaling pathway [38,39]. However, there is no direct evidence in support of the interaction between miR-744 and TGF-β1/Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found enhanced TGF-β1 facilitated bronchial epithelial cells proliferation in severe asthma. Emerging evidence suggests that miRNAs play a pivotal role in endothelial cells and detrusor fibrosis through the TGF-β1/Smad signaling pathway [38,39]. However, there is no direct evidence in support of the interaction between miR-744 and TGF-β1/Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…One notable miRNA-miR-27a-is dysregulated in both animal models of fibrosis and human fibrotic disease. [16][17][18][19] Interestingly, miR-27a has been shown to suppress fibrosis in kidney, bladder, liver and lung pathologies. [16][17][18][19] These findings suggest that targeting miR-27a could constitute a possible method to prevent cardiac fibrosis.…”
mentioning
confidence: 99%
“…Numerous studies have shown that miRNAs are involved in the tissue fibrosis process. Jing Wu et al [33] reported that miR-27a can target the AMP-activated protein kinase alpha2 catalytic subunit and activate the TGF-β1 and Smad3 signaling pathways, thereby reducing detrusor fibrosis in streptozotocin-induced diabetic rats. Su-Jin Moon et al [34] reported that FN1 is an important functional protein in the development of skin fibers.…”
Section: Discussionmentioning
confidence: 99%